Peningkatan Hasil Belajar Siswa Melalui Penerapan Model Pembelajaran Kooperatif Tipe Learning Together Pada Materi Ibadah Haji Dan Umrah Di Kelas IX.2 SMP Negeri 1 Bambel Tahun Pelajaran 2020/2021 - Pagan, Khairani (Journal of Technology and Literacy in Education, 2022)
This study aims to describe the improvement of student learning outcomes in the material for the pilgrimage and umrah through the application of a cooperative learning model of learning together type in class IX.2 of SMP Negeri 1 Bambel in the 2020/2021 school year. This research was carried out at SMP Negeri 1 Bambel in the even semester which is planned to be carried out for 3 months from January to March 2021. The subjects of this research were students of IX.2 SMP Negeri 1 Bambel in the academic year 2020/2021, totaling 29 students. This research is a classroom action research conducted for two cycles and each cycle consists of planning, action, observation and reflection stages. The data collection technique used in this study was through cycle tests and observations of teacher and student activities. The data analysis technique used in this study was descriptive qualitative which was carried out using percentage calculations. The results showed that in the pre-cycle (initial condition) the percentage of students' completeness was only 42.28%, then the first cycle after the action was carried out by applying the cooperative learning model of the Learning Together (LT) type, the percentage of completeness of student learning outcomes became 75.86% and increased by 27.58% of the initial conditions. While in the second cycle the percentage of student learning outcomes completeness increased back to 100%, an increase of 24.14%. The average teacher activity in carrying out learning in the first cycle is 3.47 and is in the sufficient criteria. While in cycle II the average value obtained is 4.67 and is in very good criteria. Has increased by 1.2. The activity of students participating in learning in the first cycle obtained a percentage of 70% which was in the sufficient criteria, while in the second cycle it increased to 90% and increased by 20%. So it can be concluded that through the application of the cooperative learning model the type of learning together can improve student learning outcomes on the material for the pilgrimage and umrah in class IX.2 of SMP Negeri 1 Bambel for the 2020/2021 academic year.